Kepemilikan Institusional, Komite Audit, Komisaris Independen, Kualitas Audit, dan Ukuran Perusahaan pada Tax Avoidance - Dhea Azella Cahyani; Faizal Satria Desitama (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The phenomenon of Panama paper case involving Indonesian companies prove the existence of tax avoidance practices. This study aims to determine the effect of institutional ownership, audit committee, independent commissioner, audit quality, and company size on tax avoidance. the energy, property & real estate, and infrastructure sectors that are listed on the IDX in 2018-2022 make up the study’s population. 168 samples were selected for this study based on sample criteria. In this study, the technique of data analysis employed was multiple linear regression analysis. This study shows that institutional ownership, audit committee and audit quality have a positive effect on tax avoidance, and company size has a negative effect on tax avoidance. The adjusted R Square value is 21 percent, the remaining 79 percent is explained by other variables.